Organic chemistry - Jones, Miatland (New York : W.W.Norton, 1997)
Chemistry and Physics
Keywords: Organic chemistry; Atom; Molecule; Stereochemistry; Alkanes; Analytical chemistry; Carbonyl chemistry; Carboxylic acid; Amines; Carbohydrates; Amino acid; Polyamino acid; Peptides; Proteins